El cuerpo hablante en la comunicación digital a partir de la reflflexión de Ortega y Gasset - Gobbi, Giulia (Scenari, 2021)
In contemporary society, marked by an incessant hypercommunication allowing us to reach even the corners of an increasingly dilated world, we find in a time that puts aside the complex dynamics of “speaking bodies”. What is a body? This evocative question was initiated by the philosopher Ortega y Gasset, who assumed a body-ego totally immersed in the factual and essential circumstance of his life. The body feels and expresses itself through gestures and expressions, symbols of a humanitas that needs to be re-discovered, especially now, in the midst of this shocking pandemic that has imposed a certain physical distance. Today, communication without community predominates since rites – symbolic actions created by “speaking bodies”, according to the contemporary phenomenologist Byung-Chul Han – have disappeared. Today more than ever, it seems very important to reflect critically on the new challenges of contemporaneity, to give way to new philosophical perspectives.